2021
DOI: 10.1097/cm9.0000000000001689
|View full text |Cite
|
Sign up to set email alerts
|

Pro-pigmentary action of 5-fluorouracil through the stimulated secretion of CXCL12 by dermal fibroblasts

Abstract: Background:There is growing evidence that 5-fluorouracil (5-FU) combined with therapeutic trauma can effectively induce skin repigmentation in vitiligo patients who are unresponsive to conventional treatments. Previous studies have mainly focused on identifying the antimitotic activity of 5-FU for the treatment of skin cancer, but few studies have investigated its extra-genotoxic actions favoring melanocyte recruitment.Methods:We utilized the full thickness excisional skin wound model in Dct-LacZ transgenic mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The increased levels of CXCL12 were observed during the wound healing of excisional or burn injuries, especially in wound margins, and the activation of the CXCL12/CXCR4 axis lead to the accumulation of eosinophil and accelerate the neovascularization and epithelialization [ 87 , 88 ]. A more recent study revealed that 5-fluorouracil (5-FU) significantly increased the CXCL12 level in the vitiligo skin, and blocking the CXCL12/CXCR4 pathway, in turn, inhibited melanocyte migration [ 89 ]. It is hypothesized that under proper injury, the CXCL12-enriched microenvironment may favor melanocyte recruitment by trafficking corresponding melanocyte precursors into the perilesional and lesional vitiligo areas to induce therapeutic effects.…”
Section: The Perspective Of Targeted Therapies In Vitiligomentioning
confidence: 99%
“…The increased levels of CXCL12 were observed during the wound healing of excisional or burn injuries, especially in wound margins, and the activation of the CXCL12/CXCR4 axis lead to the accumulation of eosinophil and accelerate the neovascularization and epithelialization [ 87 , 88 ]. A more recent study revealed that 5-fluorouracil (5-FU) significantly increased the CXCL12 level in the vitiligo skin, and blocking the CXCL12/CXCR4 pathway, in turn, inhibited melanocyte migration [ 89 ]. It is hypothesized that under proper injury, the CXCL12-enriched microenvironment may favor melanocyte recruitment by trafficking corresponding melanocyte precursors into the perilesional and lesional vitiligo areas to induce therapeutic effects.…”
Section: The Perspective Of Targeted Therapies In Vitiligomentioning
confidence: 99%
“…2 It has been widely used as a safe and effective intralesional therapy to potentialize the effects of triamcinolone to treat keloids and hypertrophic scars, 7,9 and it also improves skin color in pigmentary disorders, such as guttate idiopatic hypomelanosis 8,10 and vitiligo, 10 possibly by stimulating the secretion of CXCL12 by dermal fibroblasts. 11 Microneedling improves scars due to stimulation of neocollagenesis, angiogenesis and by reorganizing fibrosis. 5-FU has been widely…”
Section: Discussionmentioning
confidence: 99%
“…Although patient life expectancy can be significantly extended by 5-FU-based chemotherapy, drug resistance is a major barrier to the success of this treatment (19). Due to complex and heterogeneous biological processes, many of the mechanisms of chemoresistance remain elusive (20). Therefore, there is a need to identify novel biomarkers for patient selection to improve the efficacy of 5-FU.…”
Section: Discussionmentioning
confidence: 99%